Joint choice decisions - Arora, Neeraj (Henry Stewart Talks, 2010)
A novel methodology to estimate joint preference, No need to collect joint data, individual data is enough, Merges experimental design, statistical modeling and utility aggregation theories to measure joint preference, Identifies serious limitations of individual preference as a surrogate for joint preference, An empirical application involving cell phone purchase by parent teen dyads, Applies to B2B domains